After Snowden: Rethinking the Impact of Surveillance. Issue 2 (June 2014) - Bauman, Zygmunt; Bigo, Didier; Esteves, Paulo; Guild, Elspeth; Jabri, Vivienne; Lyon, David; Walker, R. B. J.
<x xml:space="preserve">Abstract</x> Current revelations about the secret US‐NSA program, PRISM, have confirmed the large‐scale mass surveillance of the telecommunication and electronic messages of governments, companies, and citizens, including the United States' closest allies in Europe and Latin America. The transnational ramifications of surveillance call for a re‐evaluation of contemporary world politics' practices. The debate cannot be limited to the United States versus the rest of the world or to surveillance versus privacy; much more is at stake. This collective article briefly describes the specificities of cyber mass surveillance, including its mix of the practices of intelligence services and those of private companies providing services around the world. It then investigates the impact of these practices on national security, diplomacy, human rights, democracy, subjectivity, and obedience.